SUARA MODERASI ISLAM DARI TAFSIR DIGITAL: Analisis Tafsiralquran.Id melalui Escape from Echo Chamber - Farida, Norma Azmi; Zainal Abidin (STAI AL-ANWAR SARANG, 2021)
This paper discusses the important role of tafsiralquran.id as a medium that voices Islamic moderation. In the current context, the voices of conservative-Islamist groups still dominate cyberspace, so it is necessary to take strategic steps to reverse the situation. This strategic move is known as the Escape from Echo Chamber movement. Echo Chamber is a digital algorithm that makes it easy to find the content according to the wishes of social media users. However, over time the Echo Chamber became a closed exclusive space. This algorithm is feared because the current condition is still dominated by conservative-Islamic groups. So, the important role of Tafsiralquran.id in voicing Islamic moderation needs to be present maximally. Moreover, digital commentary content becomes a reference because the slogan of returning to the Qur'an and hadith is increasingly existing in Indonesia. As qualitative research, this paper is described analytically. The results of this study are the Escape from Echo Chamber movement is interpreted as an effort by Tafsiralquran.id to socialize moderate digital interpretation in a real way, either through visits to educational institutions or through religious festivals typical of young people.